Modern JavaScript tools & skills. - Kolce, James; Brown, Mark; Buckler, Craig; Wanyoike, Michael; Jacques, Nilson (SitePoint, 2018)
There's no doubt that the JavaScript ecosystem changes fast. Not only are new tools and frameworks introduced and developed at a rapid rate, the language itself has undergone big changes with the introduction of ES2015 (aka ES6). Understandably, many articles have been written complaining about how difficult it is to learn modern JavaScript development these days. We're aiming to minimize that confusion with this set of books on modern JavaScript. This book outlines essential tools and skills that every modern JavaScript developer should know. It contains: A Beginner's Guide to Babel by James Kolce A Beginner's Guide to Webpack 4 and Module Bundling by Mark Brown An Introduction to Gulp.js by Craig Buckler 10 Languages That Compile to JavaScript by James Kolce 10 Must-have VS Code Extensions for JavaScript Developers by Michael Wanyoike Introducing Axios, a Popular, Promise-based HTTP Client by Nilson Jacques This book is for all front-end developers who wish to improve their JavaScript skills. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.